Burden of Mental, Neurological, Substance Use Disorders and Self-Harm in North America: A Comparative Epidemiology of Canada, Mexico, and the United States. (February 2020) - Vigo, Daniel; Jones, Laura; Thornicroft, Graham; Atun, Rifat
Objective: To estimate the burden of mental, neurological, substance use disorders and self-harm (MNSS) in Canada, Mexico, and the United States. Method: We extracted 2017 data from the Global Burden of Disease online database. Based on a previously developed framework to classify and aggregate the burden of specific disorders and symptoms, we reestimated the MNSS burden to include suicide, alcohol use, drug use, specific neurological, and painful somatic symptom disorders. We analyzed age–sex-specific patterns within and between countries. Results: The MNSS burden is the largest of all disorder groupings. It is lowest in Mexico, intermediate in Canada, and highest in the United States. Exceptions are alcohol use, bipolar, conduct disorders, and epilepsy, which are highest in Mexico; and painful somatic syndromes and headaches, which are highest in Canada. The burden of drug use disorders in the United States is twice the burden in Canada, and 7 times the burden in Mexico. MNSS become the most burdensome of all disorder groups by age 10, staying at the top until age 60, and show a distinct pattern across the lifetime. The top three MNSS disorders for men are a combination of substance use disorders and self-harm (United States), with the addition of painful somatic syndromes (Canada), and headaches (Mexico). For women, the top three are headaches and depression (all countries), drug use (United States), neurocognitive disorders (Mexico), and painful somatic syndromes (Canada). Conclusion: MNSS are the most burdensome disease grouping and should be prioritized for funding in Canada, Mexico, and the United States.